Leadership towards a just economic society - J. A. Lombard; N. J. Schoeman (Verbum et Ecclesia, 2002)
This actuality article on leadership argues for the need to move towards a just economic society. The implications of different terms are considered within a conceptual framework. This framework is essential for a better understanding of economic justice in an institutional environment, where economic relationships and economic justice has come to dominate public debate. The relations between public opinion and material wealth are analysed before justice in a mixed economy receives attention. Related conditions are discussed in succession, firstly, individual freedom and the Rule of Law, and secondly, distributive justice. The article then proceeds to discuss challenges for economic leadership in South Africa, indicating trends present in both the theoretical and political leadership current in the rest of the world. Perspective is thereby given on the situation in South African democracy, where the political focus has moved from the issue of justice as freedom, to justice in the distribution of wealth and income.